Fatores associados aos desafios da adesão vacinal infantil: percepção de profissionais de saúde. - Sousa, Darliane Kelly Barroso de (2024)
Despite the achievements that vaccination has provided in the control of vaccine- preventable diseases, the difficulty in adhering to vaccination is a fact and may be linked, among other factors, to the geographic location of the units in relation to the users' residence, social determinant factors, the interruption of supply of immunobiologicals, opening hours of vaccination rooms and, mainly, hesitancy. Vaccine hesitancy can be understood as a delay in accepting or refusing the immunobiological, even when it is available in health systems (Bedford, et al., 2018). This study aimed to analyze the factors associated with difficulty in adhering to vaccination in children aged 0 to 5 years in a territory in the municipality of Sobral. Descriptive field study of an exploratory nature and qualitative approach. The study was carried out in Sobral, located in the interior of the state of Ceará, specifically in the Dom Expedito neighborhood, a location chosen by the researcher due to her experience as an intern during her undergraduate studies. The research was carried out from July to October 2024. The study participants were ten health workers who are responsible for the direct and indirect process of vaccinating children aged 0 to 5 years. The analysis of qualitative data was carried out through thematic content analysis systematized by Bardin (2011). In the first stage, we sought meanings about the theme that the participants' statements could express, in the second stage, excerpts were cut from the participants' statements in which the main ideas were identified with the professionals' statements, and finally, a meaning was sought broader, which was discussed in the literature. It was found that the strategies used in the ESF studied have been effective in achieving high vaccination adherence in the territory. The reasons most cited by professionals in relation to challenges in vaccination adherence in the territory involve the administration of simultaneous vaccines, refusal of the COVID vaccine, sick children, mothers' lack of time, children during study hours and guardians who do not value vaccination.